2007
DOI: 10.1056/nejmoa055262
|View full text |Cite
|
Sign up to set email alerts
|

Missense Mutations in theBCS1LGene as a Cause of the Björnstad Syndrome

Abstract: BCS1L mutations cause disease phenotypes ranging from highly restricted pili torti and sensorineural hearing loss (the Björnstad syndrome) to profound multisystem organ failure (complex III deficiency and the GRACILE syndrome). All BCS1L mutations disrupted the assembly of mitochondrial respirasomes (the basic unit for respiration in human mitochondria), but the clinical expression of the mutations was correlated with the production of reactive oxygen species. Mutations that cause the Björnstad syndrome illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
181
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(190 citation statements)
references
References 29 publications
6
181
1
Order By: Relevance
“…Clinical presentations can include lactic acidosis, sensorineural loss, liver failure, LHON, developmental delay, cardiomyopathies and encephalopathy [80][81][82][83]. In addition, mutations in genes encoding CIII assembly factors have also been identified [84,85]. species production, resulting in a severe multiple systems condition [84] (Table 1).…”
Section: Oxphos Complex IIImentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical presentations can include lactic acidosis, sensorineural loss, liver failure, LHON, developmental delay, cardiomyopathies and encephalopathy [80][81][82][83]. In addition, mutations in genes encoding CIII assembly factors have also been identified [84,85]. species production, resulting in a severe multiple systems condition [84] (Table 1).…”
Section: Oxphos Complex IIImentioning
confidence: 99%
“…In addition, mutations in genes encoding CIII assembly factors have also been identified [84,85]. species production, resulting in a severe multiple systems condition [84] (Table 1).…”
Section: Oxphos Complex IIImentioning
confidence: 99%
“…Regarding complex III enzyme deficiency, two studies analyzed the impact on ROS production of mutations in the BCS1L assembly factor, involved in the insertion of the catalytic Rieske Iron Sulphur Protein (RISP) into complex III (Cruciat et al, 1999;Hinson et al, 2007;Moran et al, 2010a). One of these studies revealed defective complex III enzyme activities and respirasome assembly defects that correlated with increased superoxide levels in isolated mitochondria of lymphocytes from patients with either complex III deficiency or Björnstad syndrome (Hinson et al, 2007).…”
Section: In Mitochondrial Disordersmentioning
confidence: 99%
“…One of these studies revealed defective complex III enzyme activities and respirasome assembly defects that correlated with increased superoxide levels in isolated mitochondria of lymphocytes from patients with either complex III deficiency or Björnstad syndrome (Hinson et al, 2007). The second study was performed with skin fibroblasts from six complex III-deficient patients with BCS1L mutations, which showed a marked correlation between the severity of the enzyme deficiencies and assembly defects of the RC complexes I, III and IV and raised H 2 O 2 levels, together with an unbalanced expression of the cellular antioxidant defenses (Moran et al, 2010a).…”
Section: In Mitochondrial Disordersmentioning
confidence: 99%
“…Systemic symptoms include hepatopathy and renal tubulopathy. Mutations in the complex III assembly factor BCS1L cause GRACILE syndrome (growth retardation, aminoaciduria, cholestasis, iron overload, lactic acidosis, early death) and Bjornstad syndrome (sensorineural hearing loss with pili torti) [40][41][42].…”
Section: Complex IIImentioning
confidence: 99%